New onset atrial fibrillation and heart failure among patients with multiple myeloma: analysis from a nationwide french medical information database. (14th October 2021) - Cottin, Y; Boulin, M; Doisy, C; Mounier, M; Caillot, D; Chretien, M L; Bodin, A; Herbert, J; Bonnotte, B; Zeller, M; Maynadie, M; Fauchier, L
Abstract: Background: Over the last decade, new therapies, screening optimization, and cardiovascular management have changed the cardiovascular prognosis of patients with multiple myeloma (MM). Older studies suggested that MM could be associated with increased risk of heart failure (HF). Based on a nationwide hospitalization database, we aimed to assess the risk of hospitalization for Heart failure (HF) and/or Atrial fibrillation (AF). Methods: From 1st January 2013 to 31st December 2013, 3, 381, 472 adults (age ≥18 years) were hospitalized for any reason in French hospitals and then had at least 5 years of complete follow-up (or suffered death earlier). We identified 15, 774 patients diagnosed with known MM at baseline. The outcome analysis on hospitalization for new onset HF or AF was performed with follow-up (FU) starting at the time of last event. For each patient with MM, a propensity score-matched patient with no MM was selected (1:1) using the one-to-one nearest neighbor method (n=15774 in each group). Findings: In the propensity-score-matched population, mean±SD FU was 3.7±2.3 years, median (IQR)5.0 (1.3–5.7) years, mean age was 71±12y, and most were female (55%). When compared with patients without MM, MM patients were more likely to have history of HF (16.8% vs. 10.5%, p<0.0001), pulmonary edema (1.5 vs. 0.8%, p<0.0001), or AF (13.4% vs. 9.6%, p<0.0001). At FU, MM patients had a higher risk of all-death (yearly rate 20.02 vs 11.39%/year). Moreover, yearly rates of new onset HF or AF, which were the common CV causes of re-hospitalisation, were higher in the MM group, i.e. respectively for incidence rate, 7.47 vs 5.42%/year (p<0.0001) and 4.57 vs 3.72%/year (p<0.0001). Multivariate analysis showed that MM remained significantly associated with a higher rate of HF and AF (HR (95% CI): 1.343 (1.276–1.413) and 1.196 (1.128–1.269), respectively). Results were similar in sensitivity analysis limited to patients with recent MM (i.e. diagnosed within the 3 previous months). Interpretation: From a large nationwide hospitalization database, we show that patients with MM had a higher risk of new onset HF and AF. Our findings highlight the key issue of cardiovascular management in patients with MM. Funding Acknowledgement: Type of funding sources: None.